DAMPAK COVID -19 TERHADAP PENERAPAN PENDIDIKAN KARAKTER DAN PENDIDIKAN ISLAM - Miftahul Ulfah (Almarhalah | Jurnal Pendidikan Islam, 2021)
ABSTRACTThe spreading of a new corona virus named Covid-19 has caused so many death tolls to almost all countries in the world. Researchers suspect that this virus originated from the traditional market in China's Wuhan City selling a wide variety of fresh wet animals traded for consumption, including bats and pangolins which ultimately transmit the virus to humans. The World Health Organization has confirmed that Covid-19 transmission through droplets or sparks from infected people through talking, sneezing or coughing. With such causes, world governments recommend and even order the citizens to always maintain health and hygiene by washing hands, wearing masks, and covering mouths when sneezing or coughing. While in Islam, there are also procedures for behaving to maintain health and cleanliness. This literature study used qualitative method to examine the relevance of the global pandemic to the Islamic character education. This study then found that the influence of Covid-19 on the application of character education and Islamic education. This conclusion could be seen from the factors that influence the majority of characters carried out during the Covid-19 plague including instincts, habits, wills and conscience.Keywords: Application, Character Education, Covid-19, Islamic Education